Synthesis and Anticholinesterase Evaluation of Cassine, Spectaline and Analogues - Marcela C. R. Silva; Adriana F. L. Vilela; Carmen L. Cardoso; Ronaldo A. Pilli (MDPI AG, 2022)
In this work, twelve analogues of piperidine alkaloids (-)-cassine and (-)-spectaline were synthesized, as well as the racemic forms of these natural products. The compounds were evaluated for their inhibition of electric eel acetylcholinesterase (AChEee) and human butyrylcholinesterase (BChEhu) by on-flow mass-spectrometry-based dual-enzyme assay, and the inhibition mechanisms for the most potent analogues were also determined. Our results showed a preference for BChEhu inhibition with compounds 10c (Ki = 5.24 μM), 12b (Ki = 17.4 μM), 13a (Ki = 13.2 μM) and 3 (Ki = 11.3 μM) displaying the best inhibitory activities.